Objective assessment of the factors affecting outcome of immediate management of mandibular fractures – A prospective study in a Level-I trauma care center - Tushar Dutta; Basu, Sandip (Asian Journal of Medical Sciences, 2023)
Background: Mandibular fractures lead to complications if improperly treated. The management of mandibular fractures includes open reduction and internal fixation (ORIF) or closed reduction. Associated complications include malocclusion, infection, hardware extrusion, and nerve injury. Aims and Objectives: The aims of this study were to evaluate the functional outcome of various treatment modalities of mandibular fracture and to identify the factors affecting the outcome. Materials and Methods: The study included patients admitted in the trauma care center, between 13 and 70 years of age, and having mandibular fracture. Patients underwent ORIF or closed reduction according to the type of fracture. Mandibular injury severity score (MISS), Mandibular functional impairment questionnaire (MFIQ) score, and pain visual analog score were used to assess the functional outcome of treatment and complications. Results: Majority of the patients were male and were in the age group 21–30 years. The most common cause of fracture was road traffic accident (RTA). Majority of the patients underwent ORIF. Patients having higher injury severity scores, severe MFIQ scores and pain visual analog scores had more complications. Overall, complications in open reduction cases were higher than closed reduction ones. However, weight loss and time to functional improvement were more in closed reduction cases. Conclusion: Young males are most commonly affected with fracture of mandibles and mostly due to RTAs. There should be minimal delay from presentation to operative intervention in case of patients who require ORIF. Scoring systems such as MISS, MFIQ, and pain visual analog scale scores may help in the early prognostication of injury and warn against imminent complications.